Nucleophilic Cyclization/Electrophilic Substitution of (2,2-Dialkoxyethyl)ureas: Highly Regioselective Access to Novel 4-(Het)arylimidazolidinones and Benzo[d][1,3]diazepinones - Smolobochkin, Andrey V.; Gazizov, Almir S.; Otegen, Nazerke K.; Voronina, Julia K.; Strelnik, Anna G.; Samigullina, Aida I.; Burilov, Alexander R.; Pudovik, Michail A. (Synthesis, 2020)
Imidazolidin-2-one and 1,3-benzodiazepin-2-one scaffolds are structural motifs of many biologically active compounds. Herein, we report a highly regioselective acid-catalyzed intramolecular nucleophilic cyclization/intermolecular electrophilic substitution reaction sequence of (2,2-dialkoxyethyl)ureas. The reaction benefits from readily available starting materials, a simple workup procedure, moderate to high yields of target compounds, and provides a convenient entry to previously unknown 4-(het)arylimidazolidinones and 5-(het)arylbenzodiazepinones. The proposed mechanism of the reaction is also discussed.
Keywords: (2,2-dialkoxyethyl)ureas; imidazolidin-2-ones; 1,3-benzodiazepin-2-ones; cyclization; cyclic ureas